2017
DOI: 10.1002/adma.201704944
|View full text |Cite
|
Sign up to set email alerts
|

Energy–Structure–Function Maps: Cartography for Materials Discovery

Abstract: bonding motif that dominates the lattice energy of the framework: that is, directional coordination bonds in the case of PCPs and MOFs, or covalent bonds for COFs. The dominance of a particular arrangement of interactions allows families of structurally related or "isoreticular" [4] frameworks to be prepared because the same bonding pattern can be assumed for multiple linkers. Hence, MOFs and COFs have become enormously popular platforms for a wide variety of materials applications, enabled by the relative ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 91 publications
0
57
0
1
Order By: Relevance
“…The result is an energy-structure-function (ESF) map for each molecule, describing the likely crystal structures, their energetic stability and properties. 5 As an example of their utility, ESF maps have guided the discovery of a set of unprecedentedly low density molecular crystals with high methane storage capacity. 6 In the eld of organic semiconductors, ESF maps have been used to investigate the effect of crystal packing types on calculated carrier mobility within families of azapentacene and pyrrolebased azaphenacene molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The result is an energy-structure-function (ESF) map for each molecule, describing the likely crystal structures, their energetic stability and properties. 5 As an example of their utility, ESF maps have guided the discovery of a set of unprecedentedly low density molecular crystals with high methane storage capacity. 6 In the eld of organic semiconductors, ESF maps have been used to investigate the effect of crystal packing types on calculated carrier mobility within families of azapentacene and pyrrolebased azaphenacene molecules.…”
Section: Introductionmentioning
confidence: 99%
“…12 A recent advance in the use of computational methods to guide the discovery of functional materials is the mapping of simulated properties onto the crystal energy landscape produced by CSP methods. [13][14][15] The result, which we refer to as the energy-structure-function (ESF) map of a molecule, 13 describes the possible crystal structures, their relative stabilities and expected properties. The assessment of ESF maps of candidate molecules for a targeted function can help rule out molecules with no (or only high energy) predicted structures with the required properties and prioritize the synthesis of molecules with promising predicted structures.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the largest set of molecules that has been subjected to CSP and prop- Figure 1: The known (1) and hypothetical (2-28) molecules studied. Symmetrical (C 2v ) isomers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) are colored in orange, to contrast with the asymmetric (C s ) isomers (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…24 CSP has been combined with the prediction of optoelectronic properties to develop energystructure-function (ESF) maps. [25][26][27] These maps have been applied, for instance, to understand the impact of different packing on the charge mobility of unknown azapentacene derivatives. 26 The data confirmed that packings which maximized the π-π stacking interactions (sheet-like arrangements) also improved the charge transport and that these packings can be induced by C-H•••N bonding.…”
Section: Introductionmentioning
confidence: 99%